Interpersonal Metafunction of Webtoon Stories - Ferdiyanti, Mitha Safarani; Ekawati, Rosyida (International Journal of Systemic Functional Linguistics, 2023)
This study is concerned with the interpersonal metafunction especially the mood system in the synopses of stories in the Webtoon App. It is aimed to figure out the types of mood realized in the synopses which amount to fifteen synopses, and also their function in relation to the interpersonal meaning of the author and to the advertising means to promote the story in the Webtoon App. This research was conducted by a descriptive qualitative method. This study uses the interpersonal metafunction theory proposed by Halliday (2004). The source of data of this research is fifteen stories from three different genres – romance, thriller, and comedy in the Webtoon App. The data are sentences in the synopses of the Webtoon App’s stories that indicate the interpersonal metafunction mood element. Generally, the result of the research is the three mood types – declarative, interrogative, and imperative are found in the chosen synopses, the most dominant type of mood is the declarative mood type, while the least dominant is the declarative mood. The findings indicate that the lexico-grammar does not always reflect the interpersonal meaning fitly. It is evidenced by the finding of this research that shows the declarative is used for informing, the interrogative is used for questioning and also for informing, and the imperative is used for commands.